1998
DOI: 10.1038/sj.bjp.0702202
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adenosine receptors evoking excitation of mesenteric afferents in the rat

Abstract: 1 We examined the eects of adenosine receptor agonists and antagonists on the discharge of mesenteric aerent nerves supplying the jejunum in pentobarbitone sodium-anaesthetized rats. , i.v.) evoked increases in aerent nerve activity and intrajejunal pressure, hypotension and bradycardia. However, adenosine (3 mg kg 71 , i.v.) evoked greater increases in aerent nerve activity than bethanechol despite inducing smaller increases in intrajejunal pressure. 5 In summary, A 1 and A 2B and/or A 2B -like receptors evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
4
24
1
Order By: Relevance
“…This potential difference in the jugular nociceptive phenotype between the respiratory and gastrointestinal system may indicate that certain properties of vagal nociceptors are organ-or tissue-specific and warrants further investigation in the future. It has been previously reported that visceral spinal DRG afferent nerves are activated by adenosine (21). Our finding that the spinal DRG (i.e., neural crest-derived) afferent neurons are activated via the adenosine A 1 receptor is consistent with the previous reports in rat jejunum (6).…”
Section: Discussionsupporting
confidence: 94%
“…This potential difference in the jugular nociceptive phenotype between the respiratory and gastrointestinal system may indicate that certain properties of vagal nociceptors are organ-or tissue-specific and warrants further investigation in the future. It has been previously reported that visceral spinal DRG afferent nerves are activated by adenosine (21). Our finding that the spinal DRG (i.e., neural crest-derived) afferent neurons are activated via the adenosine A 1 receptor is consistent with the previous reports in rat jejunum (6).…”
Section: Discussionsupporting
confidence: 94%
“…There is ample evidence that activation of spinal A 1 receptors results in antinociceptive effects in a wide range of animal models, including both acute nociceptive tests and models of neuropathic and inflammatory pain (see Dickenson et al, 2000;Sawynok, 1998). There is debate as to whether A 1 receptors on peripheral sensory nerves are pro-or antinociceptive, as inhibition of PGE 2 -induced nociception (Aley et al, 1995;Aley and Levine, 1997) and stimulation of sensory afferents (Dowd et al, 1998;Kirkup et al, 1998) has been reported after A 1 receptor activation. Overall, however, the antinociceptive effects of central A 1 receptors dominate and this is confirmed in A 1 receptor gene knockout mice, which have an enhanced response to nociceptive stimuli (Johansson et al, 2001).…”
Section: Adenosine and Its Role In Painmentioning
confidence: 99%
“…Thus, whereas in rodents adenosine A 1 receptors are implicated in analgesia (see above), in humans pain-initiating actions of adenosine have been attributed to adenosine A 1 receptors (Pappagallo et al, 1993;Gaspardone et al, 1995). In addition, adenosine A 1 receptor agonists increase the firing of sensory afferent nerves (Dowd et al, 1998;Hong et al, 1998;Kirkup et al, 1998), and can cause neurogenic edema following local application in rodents Esquisatto et al, 2001). …”
Section: H Adenosinementioning
confidence: 99%